GAYA MUSIK MANTRA MINANGKABAU: STUDI KASUS NYANYIAN MANTRA MARINDU HARIMAU DI NAGARI GAUANG KECAMATAN KUBUNGKABUPATEN SOLOK - Rika Wirandi; Ediwar Ediwar; Hanefi Hanefi (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT This article aims at revealing “The Music Style of Minangkabau Spell: The Case Study of Marindu Harimau Spell Song in Gauang Village, Kubung Sub-district, Solok District.” Marindu Harimau is one of the spells used to exist in a ritual culture in Minangkabau area. This spell was practiced in order to summon tiger in a ritual management in Gauang village, Kubung sub-district, Solok district. It’s different from common spells, Marindu Harimau spell was uttered through singing performed by spell speaker called as Tukang Parindu. Method used in this research was ethnomusicology research method that involved two ways of research namely: first was fieldwork, in order to obtain the raw data of a music culture through observation, interview, and data documentation; second was desk work involving the data transcription, description, and analysis of Marindu Harimau spell song. Several theoretical concepts were used to analyze several points of problems such as ritual concept, literary theory, and music style theory. The result of this research is that Marindu Harimau spell song uses many metaphors in the arrangement of its spell text. While from the aspect of its musical style, Marindu Harimau spell song uses short tones at the end of its phrase. Its rhythm form tends to be in the free form because it follows text pattern such as conversational style or it’s also called as Parlando Rubato style. Keywords: Musical Style, Spell Song, Marindu Harimau, Ritual